The Effectof Visuospatial Perception Exercises on Motor Anticipation and Some Offensivef Skills under Pressure in Young Football Players - Yasser Jaafar Abdullah (Penerbit Jurnal Indonesia, 2025)
This study investigates the effect of special visual-temporal perception training on motor anticipation and some offensive skills under pressure among youth football players. The researcher employed the experimental method with a two-group design (experimental and control) to measure the impact of the training program while controlling for other influencing factors. The research population was deliberately selected and included the youth players of Diyala Governorate League for the 2022–2023 season, totaling 145 players. The sample consisted of 22 players from Al-Shaheed Arkan Youth Football Club, divided into an experimental group of 10 players and a control group of 10 players, randomly selected (lottery method), with goalkeepers excluded for statistical purposes. A pilot experiment was conducted on 5 players from the research population to verify the validity of the tools and procedures before actual application. The study concluded the effectiveness of visual–temporal perception training in enhancing performance and recommended adopting such programs within training plans for youth football players and conducting future research to further develop the exercises and link them to other factors affecting performance.